Self-Efficacy, Work Motivation, and Work Discipline as Predictors ‎of Science Teacher Performance: Evidence from Public Senior High ‎Schools in Enrekang, Indonesia - Karim; Anas Arfandi; Mustari S. Lamada (Yayasan Darussalam Bengkulu, 2026)
Teacher performance is associated with motivational, cognitive, and behavioral resources, but their relative contributions remain unclear across geographically diverse school settings. This study examined the associations of work motivation, self-efficacy, and work discipline with self-reported teacher performance among public senior high school teachers in Enrekang Regency, Indonesia. A quantitative cross-sectional ex post facto survey involved 101 teachers from five public schools. The multistage procedure first treated schools as clusters and then selected teachers proportionally within the participating schools. Data were obtained through four 25-item Likert-type self-report scales measuring work motivation, self-efficacy, work discipline, and teacher performance. Descriptive statistics, Pearson correlations, simple regressions, and simultaneous multiple regression were conducted using SPSS 25. In separate models, work motivation, self-efficacy, and work discipline were each positively associated with teacher performance and accounted for 43.1%, 78.0%, and 74.9% of the variance, respectively. In the simultaneous model, the three variables jointly accounted for 85.2% of the variance, F(3, 97) = 185.967, p < .001. Self-efficacy showed the largest unique association (β = .526, p < .001), followed by work discipline (β = .430, p < .001), whereas work motivation was not significant after adjustment for the other variables (β = .023, p = .683). Because teachers were nested within only five schools and clustering was not modeled, the findings should be interpreted cautiously. The results suggest that professional confidence and consistent work behavior are more closely associated with teacher performance than general motivational intensity.